If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + 6 = 2(5 + 7) + -4 Reorder the terms: 6 + 14x = 2(5 + 7) + -4 Combine like terms: 5 + 7 = 12 6 + 14x = 2(12) + -4 Multiply 2 * 12 6 + 14x = 24 + -4 Combine like terms: 24 + -4 = 20 6 + 14x = 20 Solving 6 + 14x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 14x = 20 + -6 Combine like terms: 6 + -6 = 0 0 + 14x = 20 + -6 14x = 20 + -6 Combine like terms: 20 + -6 = 14 14x = 14 Divide each side by '14'. x = 1 Simplifying x = 1
| y=500x+200 | | 8x=8x+46 | | (7a+9b+8)+(a-b+1)= | | -2-8+a=116 | | -2x^2-3x+18= | | 5x+4=8x+3 | | -70=4(a+1)-6(6a+7) | | -6=8/x | | 6u^2-10u^5v^4/6u^3y^6 | | 8x-8+3a=5ax-2a | | n/-3.2=1.6 | | 4x+24=3x+4 | | 4c+5=z-4 | | -(-6n+6)-4(1+5n)=18 | | -5x-13=38 | | 3x+2x-6=26 | | 8+-10=6 | | 11y+77=31y+62 | | 3/10x-15 | | 4m+5-3m=x | | 1/3y=1/6 | | 280^1/2 | | 24+n=19 | | 1x+5=x-7 | | 7+5s-6=7s+7-5s | | 3-12y=7y+7 | | 4/5x-48 | | (w^9)^(1/3) | | (-6)+3.98= | | 2x^3+4x^2+4x+8=0 | | 9+9m-4=7m+45-3m | | 6(r-14)+2(r-3)=14 |